Exploring Perceptions, Barriers, and Facilitators of Outdoor Physical Activity Among Muslim Women Living in Germany (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: Outdoor physical activity (PA) provides numerous health and social benefits. Despite these benefits, Muslim women often have low participation rates in outdoor PA. While previous studies have explored factors influencing Muslim women’s PA, comprehensive research specifically focused on outdoor PA within this group remains limited. This study aims to explore the perceptions, barriers, and facilitators of outdoor PA among Muslim women living in Germany.Methods: A qualitative study was conducted through semi-structured interviews with 12 Muslim women aged 23–48 years living in Germany. The interviews explored participants’ understanding of outdoor PA, attitudes, childhood experiences, perceived barriers and facilitators, and recommendations for programme development. Data were analysed using thematic analysis.Results: Participants generally viewed outdoor PA positively, defining it as exercise in urban green spaces or nature-based settings, often integrated with social activities. Key barriers identified were primarily individual and sociocultural, including fear, lack of skills, absence of companions, and safety concerns. Facilitators included skill development, women-only groups, social support, access to equipment, and culturally appropriate clothing. Main recommendations for programme development emphasised participatory approaches and skill-building.Conclusion: Early life experiences, particularly those related to access to nature and social contexts, significantly shaped women’s current perceptions, barriers, and facilitators of outdoor PAs. In contrast, religious factors did not appear to significantly influence participation. Interventions to promote outdoor PA among Muslim women should focus on skill-building, providing gradual exposure to activities, offering equipment access, and incorporating social elements. Programme developers should adopt participatory approaches to ensure cultural sensitivity and relevance.Support/Funding Source: No external funds.